Managerial narratives: a dialogical approach to understanding managerial identity - McKenna, Stephen (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to explore the use of a dialogical approach, associated with the Russian literary critic and philosopher Bakhtin, in understanding the portrayal of managerial identity in management narratives. In particular, it applies these ideas critically to understand how managers’ identities are partly shaped by the dominant discourse or idea about what a manager should “be.” Design/methodology/approach – The paper draws on three written narratives of managers. It applies a dialogical approach to consider how they position themselves interactionally in the narratives in such a way as to highlight a managerial identity based on being “enterprising” and “for change,” while simultaneously voicing alternative identities negatively. The use of the written narratives of managers and the application of a dialogical approach is an important contribution to the literature. Findings – The findings suggest that managers, when reflecting on organizational events through narrative, assume a managerial identity that reflects current dominant discourse about what a manager should “be.” In doing so they reject other possible discourses that offer alternatives, not only to managerial “being,” but also to what management and organizations might reflect and represent. The paper also, however, recognizes that some managers reject this identity and its implications for organizational activity. Research limitations/implications – The paper suggests that managerial identity is partly a product of a dominant discursive/ideological formation rather than individual choice. Although managers may reject this interpellation creating an alternative is constrained by the regime of truth that prevails about what management is at any given time. The approach might be considered overly deterministic in its view of managerial identity. Originality/value – The paper extends the understanding of managerial identity and how it is portrayed through narrative by using a dialogical approach to interpretation.